Exploring the Impact of Metaverse Tourism Technology on Alleviating Overtourism: An Integrated Approach Using TAM and TPB - Xiaoqing Jiang (SAGE Open)
With the rapid advancement of extended reality (XR) technologies, particularly virtual reality (VR) and augmented reality (AR), metaverse tourism has emerged as an innovative approach to addressing overtourism by offering immersive virtual experiences. This study empirically investigates how metaverse tourism influences tourists’ behavioral intentions, specifically exploring its potential to mitigate overtourism by shaping travel-related decision-making. By integrating the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), the study examines how perceived usefulness (PU) and perceived ease of use (PE) affect tourists’ attitudes (AT), subjective norms (SN), perceived behavioral control (PB), and ultimately their behavioral intentions (BI) to adopt metaverse tourism. Data were collected from 356 tourists who had visited popular Chinese destinations and experienced metaverse tourism. The results reveal that both PU and PE significantly influence AT, SN, and PB, with PE exerting a stronger direct impact on BI than PU. Additionally, the moderating effects of education and income levels highlight demographic variations in technology adoption behavior. This study contributes to the theoretical understanding of metaverse tourism’s role in sustainable tourism management and provides practical insights for leveraging virtual tourism technologies to optimize visitor distribution and alleviate overtourism in high-density tourist destinations.